Frequency of Insulin Resistance in People with Thyroid Dysfunction - Abdalla Elwali, Shaza; I Abdelaziz, Sulaf (Sudan Journal of Medical Sciences, 2021)
Background: Thyroid dysfunction is an endocrine disorder with a recognized association with type 2 diabetes mellitus. Thyroid hormones have a remarkable effect on glucose metabolism and can cause insulin resistance (IR). This study was aimed at assessing the relationship between IR and thyroid dysfunction. Methods: This case–control study was conducted at the endocrinology outpatient clinics of Ibrahim Malik Hospital and Omdurman Military Hospital in Khartoum State, Sudan between May 2018 and January 2019. Fasting blood glucose (FBG), fasting insulin level, and thyroid function test (TFT) were measured for each candidate and IR was estimated using the HOMA-IR equation. Results: Thirty-one patients with thyroid dysfunction and fifty-seven control participants were enrolled. The highest mean FBG was found among cases (105.3 ± 15.7 mg/dl) compared to the controls (97 ± 12.1 mg/dl), but the difference was not statistically significant (P-value = 0.598). The mean fasting insulin level was 9.22 ± 4 IU/ml in the cases and 9.4 ± 4.2 IU/ml in controls, without a significant difference (P-value = 0.681). The highest HOMA-IR score was found among cases (2.4 ± 1.2). It was 2.4 ± 1.3 in hyperthyroidism, 2.3 ± 1.1 in hypothyroidism, and 2.4 ± 1.2 in controls, and the difference was insignificant (P-value = 0.859). IR was higher in the cases (58.1%) compared to the controls (52.6%) but again not statistically significant (P-value = 0.396). Among cases, IR was encountered in 61.9% and 50% of hyperthyroid and hypothyroid patients, respectively. Conclusion: Patients with thyroid dysfunction have some level of IR that was not statistically significant when compared with controls.